Using MODIS data for the monitoring growth and development of rice plants in Red River Delta - Kham, Duong Van (VNU Journal of Science: Earth and Environmental Sciences, 2012)
Abstract . At present the unusual weather phenomenas such as droughts, floods, heat, cold damage to crops more and more increase and the level of damage is more and more increase, so the risk of crop is more and more increase if they do not timely assessment, monitoring and forecasting to overcome and mitigate damage caused by them. Identifying criterias of remote sensing for the classification and assessing land cover status had become one of the popular methods in the field of remote sensing. Along with surface observation data, the integration informations of multi time remote sensing have much resolution space and time in the calculation of vegetation indices fully capable of serving the under monitor the status and monitoring the growth , development  and formation of crop yield. Keywords: Monitoring, remote sensing indicators , rice, Red River Delta.